"Aren't These Just Young, Rich Women Doing Vain Things Online?": Influencer Selfies as Subversive Frivolity. (7th April 2016) - Abidin, Crystal
Taking seriously the global trend of selfies becoming marketable and entangled in ecologies of commerce, this article looks at Influencers who have emerged as (semi-)professional selfie-producers and for whom taking selfies is a purposively commercial, thoughtful, and subversive endeavor. Based on in-depth ethnographic fieldwork and grounded theory analysis, I examine Influencers' engagements with selfies on Instagram and their appropriations of selfies as salable objects, as tacit labor, and as an expression of contrived authenticity and reflexivity. Through these practices, Influencers achieve "subversive frivolity, " which I define as the under-visibilized and under-estimated generative power of an object or practice arising from its (populist) discursive framing as marginal, inconsequential, and unproductive.